Follow-Up Treatment After Inpatient Therapy of Patients With Unipolar Depression—Compliance With the Guidelines? - Weiß, Lukas; Zeeck, Almut; Rottler, Edit; Weiß, Heinz; Hartmann, Armin; von Wietersheim, Jörn; , The INDDEP Study Group (Frontiers in Psychiatry, 2020)
Objective: Until now, there is only a limited number of studies on the implementation of guidelines. Consequently, it was the objective of this study to determine how many patients with a major depression after hospital treatment were treated in compliance with the German treatment guideline and whether a deviation from the guideline resulted in a less favorable development. Methods: 502 patients were included; data was collected at admission and discharge from a psychosomatic (psychotherapeutic) hospital as well as three months and one year thereafter. By phone interviews and questionnaires, the clinical course and treatments were assessed. Results: 79.1% of the treatments complied with the guideline. 11.8% of the patients were treated with medication only, 60.2% with psychotherapy only, and 28.0% with a combination. There was no difference in the outcome in relation to compliance with the guideline. Cases in which the guideline was deviated had a somewhat less severe depression. Conclusion: After a treatment in a psychosomatic hospital or day hospital, the majority of depressive patients continued to receive treatment in accordance with the German guideline and with a clear focus on psychotherapy. A deviation from the guideline did not result in a less favorable course of the illness.